Structural and Radiation Shielding Properties of Dy3+ doped Phosphate Glasses - S. Kothan (2020)
© Published under licence by IOP Publishing Ltd. X - Rays has become integral and indispensable part of health care diagnosis and intervention. Which involve the risks of occupational overexposure of radiation to the patients and health care personnel. The Radiation exposure depends on "Time-Distance-Shielding". Reduction of the exposure time, increasing the distance from source proper shielding are important for protection. We need a high quality or suitable shielding material for reduction of unnecessary radiation. Although the material commonly used for radiation shielding is lead, but the environmental toxicity of lead (Pb) is a global threat that has led to the need to develop lead-free (Pb-free) and non-toxic radiation shielding glasses. In this study, the effect of Dy2O3 on physical and radiation shielding properties of 59P2O5: 10Al2O3: 20 Na2O: 10 Gd2O3: 1Dy2O3 glasses have been investigated were fabricated by melt-quenching technique. The X-rays shielding properties such as the mass attenuation coefficients (μ m ) and half value laver (HVL) of glass sample. It may also be mentioned that glass has the double function of being a radiation shielding material because of the properties of glass being transparent to visible light, absorption X-rays. Thus, the developed glasses shielding had good shielding properties, and highly practical potentials in the environmental friendly radiation shielding materials without an additional of lead.